The role of mangrove on sustaining livelihood of local community in Kg. Sungai Tinggi, Perak - Ahmad Razali, Muhamad Arifuddin (2019)
Mangrove forests are increasingly recognised as an important ecosystem in maintaining the livelihood of the locals, who live around it; but the role of mangrove forests in Kampung Sungai Tinggi has yet to be ascertained. This study provides a critical assessment of the employment opportunities locally acquired through the mangrove forest in Kampung Sungai Tinggi in the state of Perak, Malaysia. Structured questionnaires were used to collect information from households. The data obtained were analyzed using descriptive statistic while the relation between local occupation and income source was tested using Chi square. Households from the study area had benefited from the many job opportunities created from the mangroves. The economic activities involved are the fisheries sector, agriculture sector, livestock sector, trade or business, charcoal sector and other economic activities. The most common activity of the people involved are in fisheries sector which is 43%. Awareness should be based on an approach towards practicing sustainable mangrove forest management to ensure continuous mangrove life in the study area.